Ensino de notas musicais no teclado para crianças utilizando instrução baseada em equivalência de estímulos - Santiago, André Alves (Universidade Federal de São Carlos, 2021)
Teaching that uses Stimulus Equivalence-Based Instruction (EBI) has been used in research to teach different types of relations, such as reading and musical relations. This research analyzed its effectiveness in order to teaching this last type of relations in two neurotypical children and one with autism. A computerized program and a remote access program were used so the participant could have access to the instrument. The classes of the experimental stimuli were A (note name), B (keyboard note in treble clef), C (keyboard note in bass clef), D (note in the treble clef score) and E (note in the treble bass clef score). After reaching the criteria of 100% correct responses in a teaching block, the symmetry and transitivity relations between the learned stimuli were tested, as well as the emergence of the behavior of playing notes on a virtual keyboard. All participants managed to reach the last stage. The teaching program proved to be effective for teaching programmed relations and the emergence of new ones. However, when testing both the BA and DA relations, the number of correct responses in the tests decreased. It is hypothesized that is due to the concurrent teaching of relations with between stimuli that already have a previous relation.
Teaching musical notes on the keyboard to children using stimulus equivalence based instruction
Keywords: Análise do comportamento; Instrução baseada em equivalência de estímulos; Transtorno do Espectro do Autismo; Música; Behavior analysis; Stimulus equivalence-based instruction; Autism Spectrum Disorder; Music; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::PROGRAMACAO DE CONDICOES DE ENSINO